Polylactic Acide-Activated Coal Electrospun Mat Production and Characterization - Gülseren Sakarya Buluş; Merve Dandan Doğancı; Erdi Buluş; Erdinç Doğancı (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Polylactic acid (PLA) is used as a potential polymer for consumer products and biomedical applications. With the increasing environmental and sustainability concerns associated with traditional petrochemical-based polymers, PLA applications continue to increase every day. Activated carbon (A.C.) is a substance obtained by carbonization of softwood parts such as linden and willow and is used as an antidote in industrial applications because it absorbs the toxin and prevents the absorption of toxins from the small intestine into the blood. It is a toxin absorber due to its adhesion to surfaces. A.C. the biggest problem with the fact that over time, the gaseous pollutants A.C. is a gradual filling of adsorption surfaces. In this study, PLA nanofibers reinforced with biyokompozit elektrospinning technique has been secured for the production and structural (FTIR, Fourier-Transform İnfrared Spectroscopy), morphological (FEGSEM, Field Emission Gun Scanning Electron Microscope), mechanical (Tensile Test) and biological (Cell Culture) by providing a characterization of the material properties were determined. With the obtained biocomposites, it will be able to be the ideal filtration material with a longer life and a large surface area that can be used in health sector applications.